Civil Society Paradiplomacy and Multi-Level Humanitarian Governance: Evidence from MuAID in Conflict-Affected Regions - Ridwan, Wachid; Dian Ariyani Surya; Mutiara Dwi Sari (Journal of Paradiplomacy and City Networks, 2026)
This study examines the paradiplomatic engagement and humanitarian governance of Muhammadiyah Agency for International Development (MuAID) in conflict-affected regions, addressing the gap in scholarly understanding of how Indonesian civil society organizations operationalize international humanitarian assistance beyond state-centric frameworks. Employing a qualitative case study approach, this research analyzed MuAID's humanitarian programs across Palestine, Myanmar, Bangladesh, Jordan, and Turkey from 2017 to 2022 through in-depth interviews with program coordinators and local partners (n=12), document analysis, and performance assessment of five implementing institutions. The findings reveal three paradiplomatic engagement models: local NGO partnership with grant-making and capacity development; diaspora-enabled response leveraging overseas branch networks for rapid action; and domestic refugee management coordinating with government agencies for Rohingya refugees in Indonesia. Across twelve programs, MuAID delivered trauma care to 31,338 injured individuals in Gaza, educational access to 1,515 students in Myanmar, and health services to 827,181 Rohingya refugees in Bangladesh. Performance varied across models, with political constraints, administrative barriers, and funding volatility emerging as primary challenges. This research contributes to paradiplomacy and humanitarian governance scholarship by documenting Indonesian civil society organizations as humanitarian donors, reversing North-South assistance flows, and proposing a civil society paradiplomacy framework demonstrating how non-state actors leverage networks, religious identity, and grassroots partnerships to navigate political barriers in conflict-affected regions.